Community health workers' involvement in mother–child care during the 1st year after birth, in Kaya health district, Burkina Faso: A contribution analysis - Tougri, Halima; Compaoré, Rachidatou; Ouédraogo, Adja Mariam; Bila, Blandine; Temmerman, Marleen; Kouanda, Séni (Frontiers in Public Health, 2023)
Introduction: Maternal and infant morbidity and mortality remain high in sub-Saharan Africa. However, actions to strengthen postpartum care are still weak and mainly limited to health facilities (HFs). In Kaya health district, Burkina Faso, community health workers (CHWs) were involved in mother and child care during the first year postpartum through home visits, outreach sessions and accompanying mothers to health facilities. The aim of this study was to assess the contribution of CHWs to postpartum women’s attendance at the health facilities. Methods: We conducted an effect assessment using Mayne and Lemire's contribution analysis framework. Qualitative and quantitative data were collected through project documents review and individual semi-structured interviews with key-informants. Results: All the participants interviewed acknowledged that the number of women, who came to postpartum care, had increased since the implementation of the project activities. Postpartum consultation rates within the first week postpartum increased from 29% in 2011 to 80% in 2015 and from 19% to 50% within 6 weeks. Others interventions such as Performance based financing, Save The Children nutritional project and the health services component of Missed Opportunities in Mother and Infant Health (MOMI) were the alternative explanations. Conclusions: CHWs involvement in women care contributed to improve their adherence to postpartum consultations in Kaya health district.